Methodologies for assessing the acceptability of oral formulations among children and older adults: a systematic review. Issue 4 (April 2018) - Ranmal, Sejal R.; O'Brien, Fiona; Lopez, Felipe; Ruiz, Fabrice; Orlu, Mine; Tuleu, Catherine; Walsh, Jennifer; Liu, Fang
Highlights: Patient acceptability is crucial for pharmaceutical products. We review acceptability assessment methods in paediatric and geriatric patients. The published methods lack standardisation. Analysis of the differences provides insights to the design of reliable instruments. Abstract : Acceptability of medicinal products in children and older populations is pivotal in ensuring adherence and therapeutic outcomes. This review systematically identifies studies reporting on formulation aspects of oral medications that affect their acceptability in these patient groups. Particular emphasis is placed on the evaluation of the methodologies employed in the studies. Sixty-eight studies were included for analysis, with 51 (75%) in children and 17 (25%) in older populations. The studies evaluated a range of oral formulations; however, the methodologies used differ considerably in participants' characteristics, study settings, tools, acceptability definitions and criteria. It is evident that there is a lack of standardisation in study design as well as the assessment methods used in assessing acceptability of medicines in children and older populations. Teaser: This review presents a systematic analysis on methods employed for assessing acceptability of oral medicines in children and older adults, to provide insights and recommendations regarding the design of reliable instruments in future studies.